Relapse in surgically treated clubfoot: treatment approach and midterm results of revision surgery - Marinelli, Mario; Falcioni, Danya; Gigante , Antonio Pompilio; Coppa, Valentino (Acta Biomedica Atenei Parmensis, 2022)
Background and aim:The rate of recurrence of surgically early treated clubfoot is around 25% and the treatment of clubfoot recurrence remains debated. The aim of the study is to report a case series of 15 patients (16 feet) surgically treated for relapse of surgically treated clubfoot. Methods: A careful clinical and radiological evaluation of each deformity was made. The treatment algorithm was based on the pathological anatomy of the relapse, on the patient's age and on the use of a combination of surgical steps involving bones, soft tissue or both. Results: The average age of patients at the time of relapse treatment was 8 years and 6 months, with an average follow-up of 2 years. The average Avatar score was 77 (good result). The 16 feet submitted to evaluation obtained the following scores: 6 excellent, 4 good, 4 mediocre and 2 poor. Conclusions: The number of previous interventions does not seem to be related to the outcome. The clinical and radiological evaluation of the deformity is the most important step for the right application of the algorithm. The use of a treatment approach based on age and on the systematic treatment of bony and soft tissues leads to reproducible clinical results with functional improvement.